Immediate biopsy of cervical cytology‐negative and non‐HPV‐16/18 oncogenic types positive patients. Issue 4 (19th February 2018) - Karaca, İbrahim and Öztürk, Mustafa and Comba, Cihan and Demirayak, Gökhan and Alay, İsmail and Erdoğan, Volkan Şakir and Hoşgören, Murat and Yaşar, Levent
Abstract : Background: According to the American Society of Colposcopy and Cervical Pathology (ASCCP), a co‐test is recommended for patients one year after the detection of non‐HPV 16/18 viral types in association with a negative cervical cytology. In this study, we used immediate colposcopy to evaluate the risks to the patient during the one year waiting period. Methods: We included 544 Hpv‐positive/cervical cytology‐negative patients who underwent cervical cancer screening from June 2015 to June 2017. Cytological specimens were classified using the Bethesta method on a liquid based preparation. We used the Hybrid Capture 2 system to define HPV DNA. Biopsies were performed on all patients under colposcopy. Results: Three hundred and seventy‐five patients had HPV types 16/18 and 169 had non‐HPV‐16/18 oncogenic types. Of the 169 patients who had non‐HPV‐16/18 oncogenic types, 151 (89%) had no dysplasia, 16 (9.4%) had CIN 1, and 2 (1.1%) had CIN 2/CIN 3. Conclusion: For the patients who had cervical cytology negative/non‐HPV‐16/18 positive, we detected that 1.1% of these women had CIN 2‐3. For this reason, by chasing the algorithm recommended by guidelines, gynecologists take risk missing a diagnosis of CIN 2 plus lesion in 1.1% of patients.